Community Empowerment In Rumping Village: Utilising Nypa Palm (Nypa Fruticans Wurmb) For Village's Leading Products and Halal Economy - Muliyani, Muliyani; Su'aida, Nily; Lusiana, Herlina (International Journal Of Community Service, 2025)
Rumpiang Village is located in the northern part of Beruntung Baru District, Banjar Regency, South Kalimantan Province. This area is located in a low-lying plain, so most of the population works in sectors related to water and swamps. The plain of Rumpiang Village is a green area where rice fields are located, and many wild plants grow around the village, such as nipa palms, water mimosa leaves, water jasmine, water spinach, weeds, and other wetland plants. However, this local wisdom has not been utilized to its full potential due to the limited knowledge of rural communities regarding natural ingredient plants. Therefore, there is a need for education on the utilization of Nypa fruticans Wurmb plants to become the village's flagship product. The method for implementing this activity uses a participatory approach, namely socialization. Socialization to increase public knowledge, measured by pre-tests and post-tests to assess participants' initial knowledge. PKK cadres also received education regarding the halal product registration process and the siHALAL website. Knowledge regarding marketing strategies is still very limited, with an average score of 60, indicating a need for further education and guidance for PKK cadres.